Bone marrow trephine biopsy in Haematological diseases: a study of 53 cases - Khatun, Hazera; Afrose, Salma; Khan, Mohiuddin Ahmed; Ara, Tasneem; Islam, Mohammad Sirajul; Biswas, Akhil Ranjan (Journal of Dhaka Medical College, 2015)
Bone marrow aspiration (BMA) and biopsy (BMTB) are important investigations for diagnosis of haematolgical malignancies and non-malignant diseases both in adults and children. BMA and BMTB are complementary and if both are done a comprehensive analysis of bone marrow involvement is possible. 53 cases of BMTB were studied in order to underscore the indications and importance of BMTB. BMTB was done to determine cellularity in aplastic anaemia (AA) (33.96%, n=18) and in cases of failure of aspiration (32.08%, n=17). Failure of aspiration was attributable to bone marrow (BM) fibrosis (76%, n=13) due to acute leukaemia (35.30%, n=6) and myelofibrosis (43.17%, n=7). BMTB upstaged non Hodgkins lymphoma (NHL) from IIIB to IVB in 22.22% cases. 1 case of AA showed focal lymphoid aggregate which later evolved into acute lymphoblastic leukaemia (ALL). BMTB is a safe procedure and increased bleeding was noted only in a case of polycythaemia vera. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21544 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 207-210